2012
DOI: 10.1063/1.3694746
|View full text |Cite
|
Sign up to set email alerts
|

Fusion reactions from >150 keV ions in a dense plasma focus plasmoid

Abstract: Using a dense plasma focus device with a 50 kJ capacitor charge, we have observed fusion reactions from deuterium ions with record energies of >150 keV, which are confined for durations of 7-30 ns in the cores of plasmoids with typical radii of 300-500 lm and densities $3 Â 10 19 cm À3. We have for the first time simultaneously imaged the plasmoid at high (30 lm) resolution and measured trapped ion energy and neutron anisotropy. The isotropy of the neutron emission as well as other observations confirms that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 18 publications
2
27
1
Order By: Relevance
“…C. Labaune et al also have showed p-B laser fusion reactions in a two-laser beam system, where laser-accelerated proton beams hit a laser-produced boron plasma [2]. The produced plasma number density is 10 26 m −3 , whose value is higher than previous result [1].…”
Section: Introductioncontrasting
confidence: 51%
See 2 more Smart Citations
“…C. Labaune et al also have showed p-B laser fusion reactions in a two-laser beam system, where laser-accelerated proton beams hit a laser-produced boron plasma [2]. The produced plasma number density is 10 26 m −3 , whose value is higher than previous result [1].…”
Section: Introductioncontrasting
confidence: 51%
“…E. Lerner et al have showed D-D focus fusion reactions from deuterium ions with energies of more than 150 keV in a DPF device (its experiment is called FF-1) [1]. Plasmoids (high dense plasma regions) with number densities ∼ 3 × 10 25 m −3 were observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PF devices can also generate pulsed X-rays, relativistic electron beams and relatively high-energy (up to several MeVs) pulsed ion beams [1][2][3][4]. Although the produced ions are generally emitted within the z-direction of the PF device, there have been reported wide-angle angular distributions of ions [5][6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…Besides the formation and acceleration of the current sheath, the discreet characters of dense and hot pinched plasma and consequently the formation of hot spots (plasmoides) in PFs is encouraging, particularly for their use in nuclear fusion of the hydrogen-boron fuel [15,16]. Usually the final temperature and density of the focused plasma in PFs are 1 keV and 10 19 /cm 3 [17] however, the accurate mechanism in the formation of the dense structure in PFs is a challenging issue which still is an open area for more research.…”
Section: Introductionmentioning
confidence: 98%